IMPACT OF VESTIBULAR EXERCISES ON MOTOR PERFORMANCE OF FOOTBALL PLAYERS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study explores the influence of vestibular exercises on the motor performance of football players through an 8-week randomized controlled trial involving 60 professional players aged 18-30. Participants were divided into two groups: the neuro-vestibular-ocular exercise group (NVOEG, n=30) and the myofascial release group (MRHOG, n=30). The vestibular exercise program included vestibulo-ocular reflex (VOR) training, balance platform exercises, and football-specific agility drills with a ball. Results demonstrated that the NVOEG group achieved a 15-20% improvement in proprioceptive sensitivity, a 10-12% increase in agility (measured by the Zig-Zag Agility Test), a 5-7% reduction in 30-meter sprint time, and fewer landing errors (p